Teaching Reform and Practical Exploration of Molecular Pathology in a Graduate Course - Li Lisha; Hou Xiangyi; Li Yanru; Shi Ying’ai; He Xu; Chi Guangfan; Wang Yishu (Guoji laonian yixue zazhi)
Molecular Pathology is a specialized field within pathology that use molecular biology methods to investigate the mechanisms of disease initiation and progression. It is an essential component of contemporary medical graduate school. Developing an exemplary Molecular Pathology course is an essential component of contemporary medical education and a crucial element in constructing a top-notch medical education curriculum system. This paper aims to analyze the current teaching situation and identify deficiencies in order to propose strategies for teaching reform in a molecular pathology course. These strategies include updating the course content, optimizing the use of textbooks, improving teaching methodology, forming a team of high-quality teachers, establishing an evaluation and feedback mechanism, and more. The purpose is to address the development trend of the industry and meet the needs of graduate students. These reform measures are anticipated to greatly enhance the quality of teaching and serve as a helpful benchmark for the reform of medical education.